Impact of serum carotenoids on cardiovascular mortality risk in middle-aged and elderly adults with metabolic syndrome - Han, Jing; Wang, Ruiyun; Bai, Lijuan; Liu, Yun; Liao, Man; Zhang, Liting; Liu, Lihua; Qi, Benling (Frontiers in Nutrition, 2024)
Background Metabolic syndrome (MetS), characterized by abdominal adiposity, hypertension, hyperglycemia, and dyslipidemia, is associated with dysregulated immune function, elevated oxidative stress, and chronic low-grade inflammation. Aging exacerbates insulin resistance and the prevalence of MetS. Dietary antioxidants, such as carotenoids, may play a role in preventing cardiovascular disease (CVD) mortality, but evidence remains mixed, particularly among middle-aged and elderly individuals with MetS. Methods We analyzed data from 6,601 participants aged 40 years and above with MetS from the National Health and Nutrition Examination Survey (NHANES) III (1988–1994) and NHANES 2001–2006 cycles. Serum concentrations of α-carotene, β-carotene, lycopene, β-cryptoxanthin, and combined lutein/zeaxanthin were quantified. Participants were followed for a median of 16.8 years. Cox proportional-hazards models were used to assess the association between serum carotenoid concentrations and CVD mortality risk, with adjustment for potential confounders. Results During the follow-up period, 1,237 CVD deaths were identified. Analysis revealed an inverse dose–response relationship between serum lycopene levels and cardiovascular mortality risk. Compared to the lowest quartile, the multivariable-adjusted hazard ratios (95% confidence intervals) for ascending quartiles of serum lycopene were 0.84 (0.71, 1.00), 0.87 (0.74, 1.03), and 0.77 (0.61, 0.97), with a significant trend (p = 0.039). No significant associations were observed for other carotenoids. Conclusion In this prospective cohort study of 40-year-old and older individuals with MetS, we observed an inverse association between serum lycopene levels and CVD mortality risk.